2020
DOI: 10.3390/ijerph17238926
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Under-Nutrition and Hypertension among Ellisras Children and Adolescents Aged 9 to 17 Years

Abstract: Background: Globally, under-nutrition and hypertension in children has been associated with the risk of developing cardiovascular disease (CVD) in adulthood. The main objective of this study was to investigate the relationship between under-nutrition and hypertension, furthermore, to determine the risk of developing hypertension due to under-nutrition. Methods: The study comprised of 1701 participants (874 boys and 827 girls) between the ages of 9 and 17 years old. All anthropometric and blood pressure measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
2
0
0
Order By: Relevance
“…In the current study, we found significant correlations between MUAC and both SBP and DBP, which is consistent with the findings of Mazicioglu et al [ 56 ], Ma et al [ 57 ], and Mphahlele et al [ 58 ]. However, in the Sardinian Hypertensive Adolescent Research Programme study, MUAC significantly correlated with SBP but not with DBP [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we found significant correlations between MUAC and both SBP and DBP, which is consistent with the findings of Mazicioglu et al [ 56 ], Ma et al [ 57 ], and Mphahlele et al [ 58 ]. However, in the Sardinian Hypertensive Adolescent Research Programme study, MUAC significantly correlated with SBP but not with DBP [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our result showed adolescent with an increase of one BMI kg/m 2 was 1.12 times at risk of developing hypertension, that is, increase in one BMI kg/m 2 contributed by 12% of developing blood pressure among adolescents. Similar to our study, other studies have shown a positive association between adolescent hypertension and increasing BMI 10 14 24 28 29. In South Africa, a study included 1665 schoolchildren and adolescents (846 boys and 819 girls) aged 5 to 15 years showed an increase of one BMI kg/m 2 was associated with 1.198 times and 1.23 times risk of developing systolic and diastolic hypertension, respectively 24…”
Section: Discussionsupporting
confidence: 89%
“…Não obstante, a desnutrição também foi associada positivamente à HAS em uma amostra de crianças e adolescentes Sul-Africanas. 27 A FCR elevada foi considerada fator de risco para desenvolvimento de HAS, visto que essa informação já era estudada na população adulta com sérias consequências à saúde e com este estudo confirma-se essa relação também na população pediátrica. 70 Houveram estudos que relacionaram fatores bioquímicos ao desenvolvimento da HAS, como o estudo de Ding, 65 que investigou prospectivamente o papel potencial das adipocinas na associação entre o fenótipo MHO e HAS em crianças e adolescentes, e os achados desta pesquisa foram que os indivíduos MHO com adipocinas anormais apresentaram uma probabilidade significativamente maior de desenvolver HAS.…”
Section: Discussionunclassified